Reliability and validity of the Oxford happiness inventory among university students in Iran - Javad Liaghatdar, Mohammad; Jafari, Ebrahim; Reza Abedi, Mohammad; Samiee, Fatemeh (The Spanish Journal of Psychology, 2008)
The aim of the present study was to examine the internal reliability, content validity, construct validity, and concurrent validity of the Persian translation/Farsi version of the Oxford Happiness Inventory. The Oxford Happiness Inventory and Fordyce Happiness Inventory were completed by a sample of 727 Iranian university students. Findings confirmed the internal reliability, construct, and concurrent validity of the Oxford Happiness Inventory. Thus, it can be recommended for use as a trait-measure of happiness among Iranian samples.